Build your own universal computer interface - Chubb, Bruce A. (McGraw-Hill, 1997)
This will be the second edition of TAB's bestselling title on building your own universal computer interface. This edition will update the information on the step-by-step instructions for building a truly universal computer interface system (UCIS). The disk will contain all of the code needed to implement the hardware.